2020
DOI: 10.1002/jcph.1749
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Therapeutic Anticoagulation and Mortality in Critically Ill Patients With Respiratory Failure From SARS‐CoV‐2: A Retrospective Cohort Study

Abstract: The pathophysiology of respiratory failure associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains under investigation. One hypothesis is that progressive endothelial damage from the virus leads to microvascular thrombosis. It is uncertain if empiric therapeutic anticoagulation provides benefit over standard deep vein thrombosis (DVT) prophylaxis in critically ill patients with SARS-CoV-2. A retrospective cohort study was performed to evaluate adult patients admitted to the intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 15 publications
0
50
0
Order By: Relevance
“…Results from previous studies investigating the role of anticoagulation among patients with covid-19 have varied 13143031323334353637. Variations in reported associations probably derive from different definitions of anticoagulation, for both drug type and dose.…”
Section: Discussionmentioning
confidence: 98%
“…Results from previous studies investigating the role of anticoagulation among patients with covid-19 have varied 13143031323334353637. Variations in reported associations probably derive from different definitions of anticoagulation, for both drug type and dose.…”
Section: Discussionmentioning
confidence: 98%
“…39-41 Retrospective studies of therapeutic-compared to prophylactic-dose anticoagulation have reported mixed effects on mortality, while only two small studies have examined outcomes with intermediate-compared to prophylactic-dose anticoagulation, largely focusing on venous thromboembolism rates, again with conflicting results. 7,15,16,18-22,42,43 More recently, the ACTIV randomized clinical trial showed futility of therapeutic-compared to prophylactic-dose anticoagulation in critically ill COVID-19 patients, leading to a pause in further recruitment of critically ill patients for that trial. Our analysis is the first large-scale study to specifically examine intermediate- and prophylactic-dose anticoagulation in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective secondary analysis of 141 intubated COVID-19 patients from three hospitals in the United States found no difference in 28day mortality from time of intubation when empirically treated with therapeutic dose anticoagulation compared with standard DVT prophylactic doses, even among those with D-dimer levels > 2 μg/mL. 38 As only intubated patients were included, it is unclear whether therapeutic anticoagulation in a general medical ward may reduce progression to intubation or incidence of VTE. A retrospective study from the United States analyzed 3,625 COVID-19 patients with moderate or severe illness finding that therapeutic anticoagulation including apixaban has similar efficacy to enoxaparin in decreasing mortality in hospitalized COVID-19 patients.…”
Section: What Type Of Venous Thromboembolism (Vte) Prophylaxismentioning
confidence: 99%